Salivary cortisol and testosterone variations during an official and a simulated weight-lifting competition - Passelergue, P.; Robert, A.; Lac, G. (International Journal of Sports Medicine, 1995)
This study was undertaken to compare salivary levels of cortisol (C), testosterone (T) and T/C ratio during an official and a simulated weight-lifting competition. Thirteen top-level weight-lifters (French team) including 7 national level athletes (NG) and 6 international level athletes (IG) entered the study. The performance levels corrected with the IWF index (an index which relates the performance to body weight) obtained during the competition were higher than those obtained during the simulation and were higher in IG than in NG. Salivary samples were collected for each session after weighing, snatch and clean-and-jerk. The mean T-levels of these athletes were the same as those obtained in the laboratory on sedentary adults; they did not vary throughout the competition, nor between the competition and the simulation. Conversely the C-levels were statistically higher in the competition than in the simulation (p < 0.05). These C-levels are correlated with the performance levels corrected with the IWF index obtained during the competition (r = 0.67; p < 0.05; n = 13). Moreover, C-levels noted at the time of the competition were higher in the international athletes than in the national ones. Therefore, we concluded that the cortisol level may be considered as a performance factor in weight-lifting.